LEGAL ENTITIES IN CORPORATE CRIME AND ITS IMPLICATIONS FOR LEGAL CERTAINTY: A STUDY OF LAW ENFORCEMENT AGAINST BUSINESS ENTITIES - Fadlan (Journal of International Islamic Law, Human Right and Public Policy, 2025)
The abuse of legal personality in corporate crime has become an increasingly complex phenomenon in line with the development of the business sector and modern corporate structures. Legal entities, which are fundamentally established to facilitate economic activities and provide legal certainty, are in practice often misused as instruments to evade legal liability, whether through engineered business structures, artificial separation of assets, or the shifting of responsibility to specific individuals. Such conditions give rise to serious problems concerning legal certainty, particularly in the enforcement of law against business entities as subjects of law. This study aims to analyze the forms of abuse of legal personality in corporate crime and their implications for legal certainty within the law enforcement system in Indonesia. The research employs a normative legal research method with a statutory approach and a conceptual approach, supported by an examination of court decisions related to the enforcement of law against business entities. The data are analyzed qualitatively to assess the consistency in the application of the principles of corporate liability and the effectiveness of the sanctions imposed. The findings indicate that the abuse of legal personality in corporate crime remains difficult to address optimally due to weak interpretations of the concept of corporate liability and a law enforcement tendency that focuses primarily on individual perpetrators. This condition results in low legal certainty and the failure to achieve the objectives of justice and deterrence for corporations. Therefore, it is necessary to strengthen law enforcement through progressive legal interpretation, the application of the piercing the corporate veil principle, and the harmonization of regulations on corporate liability in order to ensure legal certainty and corporate accountability.